Isolation and molecular identification of salt tolerant probiotic bacteria and their impacts on rice (Oryza sativa) seedlings - Rahman, Mahmud -Ur (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Master of Science in Biotechnology, 2022.